Zmiany w użytkowaniu mleka w wybranych zakładach mleczarskich - Sokołowski, Tadeusz; Kaniecka, Monika (Changes in the Utilization of Milk in Selected Dairy Plants, 2005)
Adjusting dairy production standards to the requirements of the European Union had a positive effect on quality, season ability and fat utilization at the dairy plants examined in the study. A decrease in milk purchase and an increase in protein utilization were recorded at dairy plant I, which has already adjusted its standards to meet the EU regulations. At plant II, which plans to complete the adjustment process in 2005, milk purchase increased by 20% and protein utilization decreased.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 275-279